2011
DOI: 10.1186/1471-2458-11-187
|View full text |Cite
|
Sign up to set email alerts
|

Good practice in health care for migrants: views and experiences of care professionals in 16 European countries

Abstract: BackgroundHealth services across Europe provide health care for migrant patients every day. However, little systematic research has explored the views and experiences of health care professionals in different European countries. The aim of this study was to assess the difficulties professionals experience in their service when providing such care and what they consider constitutes good practice to overcome these problems or limit their negative impact on the quality of care.MethodsStructured interviews with op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
279
2
32

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(332 citation statements)
references
References 28 publications
19
279
2
32
Order By: Relevance
“…[3] Mental health problems in UMs are reported in the international (primary healthcare) literature, but little is known about the problems Greek GPs encounter in UMs. [3,5,[15][16][17] The aim of the study was to gain insight in how Greek GPs cope with UMs with mental health problems, the barriers and levers encountered and solutions applied. We anticipate that the results of this study will be useful for the policy makers when the primary healthcare reform is under development.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Mental health problems in UMs are reported in the international (primary healthcare) literature, but little is known about the problems Greek GPs encounter in UMs. [3,5,[15][16][17] The aim of the study was to gain insight in how Greek GPs cope with UMs with mental health problems, the barriers and levers encountered and solutions applied. We anticipate that the results of this study will be useful for the policy makers when the primary healthcare reform is under development.…”
Section: Introductionmentioning
confidence: 99%
“…The literature search and interviews with experts found that in order to provide compassionate care crucial problems and barriers occur at the levels of professional, patient, and organisation. Many studies identified the training of professionals in culturally sensitive aspects of care as a core enabler or a critical element of improvement interventions [6,[12][13][14][15].…”
Section: Highlights From the Ecm: The Need For Compassionate Carementioning
confidence: 99%
“…Previous reports suggested that in the ED seting, where it is not possible to establish a post-acute therapeutic relationship with the migrant patient, it is likely that personality disorders are underestimated [52].…”
Section: Axis IImentioning
confidence: 99%